Optimal control of a hyperbolic system that describes Slutsky demand - Milchenko, Olha (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2021)
A non-linear optimal control problem for a hyperbolic system of first order equations on a line in the case of degeneracy of the initial condition line is considered. This problem describes many natural, economic and social processes, in particular, the optimality of the Slutsky demand, the theory of bio-population, etc. The research is based on the method of characteristics and the use of nonstandard variations of the increment of target functional, which leads to the construction of efficient computational algorithms.